Incorporation of Greater Palatal Artery Pathway Projection into a Static Surgical Guide - Alexandru E. Petre; Andrei Macris; Cezar Ionita; Gabriel Cojocariu; Sergiu Drafta (Dentistry Journal)
Background/Objectives: The purpose of this study was to develop a digital workflow to incorporate the mucosal projection of the pathways of the greater palatal artery into a static surgical guide used for free gingival graft harvesting and connective-tissue grafting techniques. Methods: A cone-beam computed tomography file was uploaded and segmented using specific tools from digital design software. The artery pathways were identified and marked on cone-beam computed tomography. A standard tessellation file format was obtained and uploaded into three-dimensional mesh-processing software; this was merged into an intraoral scan file. New files were obtained and uploaded into three-dimensional modeling software. The final model with projections of the artery pathways was generated using specific tools. The digital model was uploaded into guided surgery planning software to design a digital surgical guide that could later be printed with the artery pathways marked on its surface. Results: The static surgical guide to the palatal mucosa could be used during a surgical approach for marking the safe-zone area against the artery pathways. Conclusions: The proposed technique is a viable method for visualization and marking the artery pathway projection on a static surgical guide when performing free gingival graft harvesting and connective-tissue grafting techniques.